2019
DOI: 10.1111/jfs.12684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan with vegetable oil on shelf life of brown trout (Salmo trutta fario) fillets fed on prebiotics

Abstract: In this research, effects of chitosan coating of brown trout (Salmo trutta fario) fillets containing inulin were determined. Chitosan enriched by vegetable oils (0% Chitosan‐control, 2% acetic acid +Chitosan, 2% sage oil+Chitosan, and 2% mint oil+Chitosan) on shelf life was investigated. In the experiment, fish fillets from the control and the experimental groups were subjected to chemical and microbiological analyses at 0, 3, 6, 9, and 12 days of cold storage at 4 ± 1°C. Coating with chitosan enriched with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…These results are in agreement with other studies which report PTC reduction with the addition of plant extracts or EOs in fish (Vieira et al, 2019;Rezaeifar et al, 2020). Similarly, it was reported that chitosan coatings combined with thyme EO (Chamanara et al, 2013), sage and mint oils (Yumuk et al, 2019), and propolis extract (Ebadi et al, 2019), could reduce TVC and PTC values on the surface of fish fillets. Also, Raeisi et al (2020) reported that among three EO (peppermint, tarragon and thyme) combined with chitosan coating, on day 12, the best results were obtained in trout fillet coated with chitosan and thyme EO which led to a reduction of 2.2 log CFU/g compared to control and the others EO led to a reduction of 1 to 1.77 log CFU/g.…”
Section: Ptcsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with other studies which report PTC reduction with the addition of plant extracts or EOs in fish (Vieira et al, 2019;Rezaeifar et al, 2020). Similarly, it was reported that chitosan coatings combined with thyme EO (Chamanara et al, 2013), sage and mint oils (Yumuk et al, 2019), and propolis extract (Ebadi et al, 2019), could reduce TVC and PTC values on the surface of fish fillets. Also, Raeisi et al (2020) reported that among three EO (peppermint, tarragon and thyme) combined with chitosan coating, on day 12, the best results were obtained in trout fillet coated with chitosan and thyme EO which led to a reduction of 2.2 log CFU/g compared to control and the others EO led to a reduction of 1 to 1.77 log CFU/g.…”
Section: Ptcsupporting
confidence: 93%
“…These results are in agreement with other studies which report PTC reduction with the addition of plant extracts or EOs in fish (Vieira et al ., 2019; Rezaeifar et al ., 2020). Similarly, it was reported that chitosan coatings combined with thyme EO (Chamanara et al ., 2013), sage and mint oils (Yumuk et al ., 2019), and propolis extract (Ebadi et al ., 2019), could reduce TVC and PTC values on the surface of fish fillets. Also, Raeisi et al .…”
Section: Resultsmentioning
confidence: 99%
“…But it is a potential protective additive with proven antimicrobial activity against foodborne bacteria, molds, and fungi. It is thought that having polycationic properties plays a role in its antimicrobial effect 5,6 . The fact that it is biodegradable and biopermeable and does not have a negative effect on health makes Ch a special product 1 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Ch is also used in cases such as increasing the natural flavor and emulsifying effect, stabilizing the color, and in deacidification. In recent years, edible‐coating‐based studies have been increasing on the development of the protective effect and shelf life of Ch, its ability to integrate with different preservation techniques and preservatives 5,7‐9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation